MINDFULNESS DENGAN TEKNIK STOP UNTUK MENCEGAH DOOMSCROLLING PADA DEWASA AWAL - Navissa Akmalia; Fisa Amanah; M. Hubbal Khair (Institut Agama Islam Sumatera Barat, 2026)
The digital era is characterized by unlimited access to information via social media, and now has fundamentally transformed news consumption patterns. While algorithmic curation and the delivery of relevant content can facilitate information retrieval, they may also undermine an individual’s capacity for self-regulated social media usage. An emergent phenomenon known as 'doomscrolling' encompasses compulsive behaviors driven by excessive scrolling and algorithmically generated content. This study investigates cognitive awareness and preventative strategies for doomscrolling through mindfulness-based techniques to mitigate the adverse effects of prolonged exposure to negative media content. The study involved 22 participants within the age range of 19–27 years. The findings indicate a significant increase in participants' cognitive awareness regarding doomscrolling, although challenges in reducing overall social media consumption persist.